Casino Luxembourg - Forum d'Art Contemporain. - Assenmaker, Michel; Bay, Didier; Bernard, Laurence; Bovier, Lionel; Ceysson, Bernard; Charrueau, Delphine; Chua-Bernard, Laurence; Colpitt, Frances; Dupuis, Claude; Fuchs, Rudi, H.; Heldenstein, Bettina; Herzog, Hans-Michael; et al. (Luxembourg : Casino Luxembourg - Forum d'Art Contemporain, 1998)
Casino Luxembourg - Artistes - Expositions - Textes & documents - Forum - Programme culturel
Adami, Valerio ; Alechinsky, Pierre ; Anselmo, Giovanni ; Atlan, Jean-Michel ; Bay, Didier ; Caulfield, Patrick ; Convert, Pascal ; Cloots, Martine ; Combas, Robert ; Cragg, Tony (Anthony) ; Deacon, Richard ; Debré, Olivier ; De Gobert, Philippe ; Delvoye, Wim ; Downsbrough, Peter ; Di Matteo, Gabriele ; Fabre, Jan ; Falaguasta, Filippo ; Hélion, Jean ; Jugnet, Anne Marie ; Knoebel, Imi ; Milin, Robert ; Mucha, Reinhard ; Oursler, Tony ; Prum, Antoine ; Schön, Andreas ; Scully, Sean ; Steins, Hermann ; Toderi, Grazia ; Veneman, Peer ; Vermeiren, Didier ; Viallat, Claude ; Wall, Jeff ; West, Franz ; Wurm, Erwin ; Dorner, Helmut ; Snyder, Christian Bernard . Hilla ; Decker, Simone ; Goldin, Nan ; Raynaud, Patrick ; Armleder, John
Biografie
Frans
boek